Menstrual phase-dependent differences in neurobehavioral performance: the role of temperature and the progesterone/estradiol ratio. Issue 2 (31st October 2019) - Grant, Leilah K; Gooley, Joshua J; St Hilaire, Melissa A; Rajaratnam, Shantha M W; Brainard, George C; Czeisler, Charles A; Lockley, Steven W; Rahman, Shadab A
Abstract: Study objectives: Women in the luteal phase of the menstrual cycle exhibit better cognitive performance overnight than women in the follicular phase, although the mechanism is unknown. Given the link between core body temperature (CBT) and performance, one potential mechanism is the thermoregulatory role of progesterone (P4), estradiol (E2), and their ratio (P4/E2), which change across the menstrual cycle. We examined the role of P4/E2 in modulating performance during extended wake in premenopausal women. Additionally, we compared the acute effects of nighttime light exposure on performance, CBT, and hormones between the menstrual phases. Methods: Participants were studied during a 50 h constant routine and a 6.5 h monochromatic nighttime light exposure. Participants were 16 healthy, naturally cycling women (eight follicular; eight luteal). Outcome measures included reaction time, attentional failures, self-reported sleepiness, CBT, melatonin, P4, and E2. Results: As compared to women in the luteal phase, women in the follicular phase exhibited worse performance overnight. CBT was significantly associated with performance, P4, and P4/E2 but not with other sex hormones. Sex hormones were not directly related to performance. Light exposure that suppressed melatonin improved performance in the follicular phase ( n = 4 per group) to levels observed during the luteal phase and increased CBT but without concomitant changes in P4/E2. Conclusions: Our results underscore the importance of considering menstrual phase when assessing cognitive performance during sleep loss in women and indicate that these changes are driven predominantly by CBT. Furthermore, this study shows that vulnerability to sleep loss during the follicular phase may be resolved by exposure to light.